2016
DOI: 10.5430/jnep.v6n12p24
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of elders about sexuality

Abstract: Background: Sexuality has been considered as one of the most natural and main aspects of life that affect an individual's identity as a human being. Not only the sexual activity provides happiness for older adults, it may also maintain a sense of self-esteem. Until recently, little attention was paid to sexuality of elderly people in many countries. Aim of the study was to identify knowledge, attitude and practice of elders about sexuality. Methods: Descriptive design: This study was administered in three elde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
(59 reference statements)
2
2
0
Order By: Relevance
“…Thus, individuals with higher levels of knowledge have more permissive attitudes towards older adults' sexuality. This finding is similar to the results of the study by Lee Kyung-Ja et al 49 , Mahieu et al 50 and Senra 51 , but different from the findings of Alam and Fadila 48 , who did not find a significant correlation between the scores of knowledge and attitudes.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Thus, individuals with higher levels of knowledge have more permissive attitudes towards older adults' sexuality. This finding is similar to the results of the study by Lee Kyung-Ja et al 49 , Mahieu et al 50 and Senra 51 , but different from the findings of Alam and Fadila 48 , who did not find a significant correlation between the scores of knowledge and attitudes.…”
Section: Discussionsupporting
confidence: 82%
“…Data from this study showed that people with more advanced education have a high level of knowledge about sexuality, as reported by Alam and Fadila 48 . Individuals with many years of schooling have greater access to primary care services and, consequently, more significant contact with sexuality-related information, besides better assimilating guidance by professionals 54 .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Although up to 8% of the total population will be elders by 2030, even so most people consider even the idea of sexuality of elderly people as absurd [6].…”
Section: Introductionmentioning
confidence: 99%